Investigation of the landslides in Beylikduzu-Esenyurt Districts of Istanbul from InSAR and GNSS observations - Bayik, Caglar; Abdikan, Saygin; Ozdemir, Alpay; ArIkan, Mahmut; Sanli, Fusun Balik; Dogan, Ugur (SPRINGER, 2021)
This study aims to detect recent landslide displacements caused by geological structure of the region where there is intense urbanization using advanced Interferometric Synthetic Aperture Radar (InSAR) techniques and with Global Navigation Satellite Systems (GNSS) observations in the Beylikduzu and Esenyurt districts in Istanbul megacity, Turkey. In this study, multiple satellites with different frequencies (C-band, L-band) and periodic GNSS observations were employed. For the entire peninsula, we processed 149 images from the ascending orbit, 144 images from the descending orbit of Sentinel-1 (C-Band) and 24 ALOS-2 (L-band) images from the ascending orbit. The evaluations were carried out in the period between 2015 and 2020 for Sentinel-1 imagery and 2015-2020 for ALOS-2 imagery respectively. Since the study area is covered by dense settlements, the Persistent Scatterer InSAR (PSI) technique was utilized to determine the landslide behaviors. According to the results, for both orbits of the Sentinel-1, the horizontal displacement and the vertical displacement were observed in the range of - 10 to 6 mm. Compared to the magnitude of displacement signal measured by Sentinel-1, ALOS-2 data has higher values due to the high surface penetration of the L-band. The results showed that most of the old landslide regions are reactivated. Horizontal movement derived through Sentinel-1 showed that the highest movement overlaps with old landslides. L-band ALOS-2 provided better spatial coverage of landslide movement than C-band Sentinel-1 data, especially at the rural part along the coast of the lake.
Keywords: InSAR; GNSS; Landslides; Multi-temporal SAR; Time series; PERSISTENT SCATTERER INTERFEROMETRY; BUYUKCEKMECE LANDSLIDE; PERMANENT SCATTERERS; TURKEY; SAR; AREA; EARTHQUAKE; DEFORMATION; SUBSIDENCE; REGION; Geology; Meteorology & Atmospheric Sciences; Water Resources